ByzRev 02.2020.033: Eleftherios Despotakis, John Plousiadenos (1423?–1500): A Time-Space Geography of his Life and Career: (Orientalia Lovaniensia Analecta 284; Bibliothèque de Byzantion 21). Leuven – Paris – Bristol: Peeters 2020. - Yost, Charles C. (The Byzantine Review, 2020)
Eleftherios Despotakis, John Plousiadenos (1423?–1500): A Time-Space Geography of his Life and Career (Orientalia Lovaniensia Analecta 284; Bibliothèque de Byzantion 21). Leuven – Paris – Bristol: Peeters 2020. 222 pp. – ISBN: 978-90-429-3787-1 (€ 90).